Research on visual communication form of Shenyang subway advertisement - Sun, Ji (Transactions on Social Science, Education and Humanities Research, 2024)
In the context of the background of new media development, the speed of information transmission increases. Subway advertising, as an important form of advertising, has distinct characteristics in the level of visual communication. Subway advertising plays a role in shaping urban cultural image and releasing information, and has its own unique features compared with traditional forms of advertising. The development of subway also creates a favorable space for the innovative development of advertising, and forms a unique way of visual communication of advertising. This paper mainly expounds the main forms and contents of the visual communication of subway advertising from the theoretical level, and then explores in detail the existing problems of Shenyang subway advertising and the direction and development measures of visual communication. Through in-depth research from the theoretical level, it can provide beneficial reference for the development of Shenyang subway advertising visual communication.